Comparison study of the performance of two kinds of photovoltaic/thermal(PV/T) systems and a PV module at high ambient temperature. (1st April 2018) - Yuan, Weiqi; Ji, Jie; Li, Zhaomeng; Zhou, Fan; Ren, Xiao; Zhao, Xudong; Liu, Shuli
Abstract: The power output of a PV system decreases with the operating temperature rising especially in summer. Using the photovoltaic/thermal(PV/T) can help cooling down the operating temperature of the cells. However, there are few studies comparing the performance of different PV/T systems and the PV module at high ambient temperature. In this study, a series of experiments were conducted to compare the performance of the water-pipe-based PV/T, the PV/T with micro-channel heat pipe array(MHPA) and the conventional PV module at high ambient temperature. The results showed that the average cell temperature of the water-pipe-based PV/T, the PV/T with MHPA and the PV module rose in the morning and fell in the afternoon. The temperature of the three systems could be up to 70 °C, 90 °C and 100 °C respectively, while the electrical efficiency of the three systems decreased with the increment in the temperature of the PV cells and ranged from 11.2% to 10%, 9.6%–7.7% and 8.6 to 7.0% respectively. It means that both the water-pipe-based PV/T and the PV/T with MHPA could improve the performance of PV cells. However, in this study the water-pipe-based PV/T had better performance than the PV/T with MHPA. Highlights: A comparison experiment of different PV/T systems was proposed. Both the water-pipe-based PV/T and the PV/T with MHPA could improve the performance of PV cells. The performance of the water-pipe-based PV/T is better than the PV/T with MHPA with this paper's design. The temperature distribution of the PV/T with MHPA is more stable and uniform.